Answer:
see explanation
Explanation:
Multiply through by the lowest common multiple of u, v and f, that is uvf
uvf ×
+ uvf ×
= uvf ×
, that is
uf + vf = uv ← factor out f on the left side → (1)
f(u + v) = uv ← divide both sides by (u + v)
f =
![(uv)/(u+v)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xdwytwuil27c8ms7e8wrbwx7oja9qnnfbe.png)
(b)
Using line (1)
uf + vf = uv ( subtract uv from both sides )
uf + vf - uv = 0 ( subtract uf from both sides )
vf - uv = - uf ← factor out v on the left side
v(f - u) = - uf ← divide both sides by (f - u)
v = -
![(uf)/(f-u)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8tu93kg96ky88zsb4j23ff6ssezln136t2.png)